2019
DOI: 10.1111/dom.13896
|View full text |Cite
|
Sign up to set email alerts
|

Impact of baseline characteristics and beta‐cell function on the efficacy and safety of subcutaneous once‐weekly semaglutide: A patient‐level, pooled analysis of the SUSTAIN 1‐5 trials

Abstract: Aim To evaluate the impact of relevant patient‐level characteristics on the efficacy and safety of subcutaneous, once‐weekly semaglutide in subjects with type 2 diabetes. Materials and Methods Exploratory post hoc analyses of pooled SUSTAIN 1‐5 (phase 3a) randomized, controlled trials examined the change from baseline in HbA1c and body weight (BW), and the proportions of subjects achieving the composite endpoint (HbA1c < 7.0% [53 mmol/mol]), without weight gain or severe/blood glucose‐confirmed symptomatic hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
4
14
0
2
Order By: Relevance
“…Changes in weight across all dulaglutide dose groups, as well as dose‐related treatment differences in weight loss, were larger among patients with lower (<8.5% [69 mmol/mol]) versus higher (≥8.5%) baseline HbA1c. This is consistent with prior studies suggesting an inverse relationship between the magnitude of GLP‐1 RA‐mediated weight loss and baseline HbA1c 21,29,30 . The physiological basis for this phenomenon is not clear, but could be related to greater reductions in energy loss through glucosuria following greater improvements in glycaemic control observed in the higher baseline HbA1c subgroup (and thus poorer baseline glycaemic control) compared with the lower baseline HbA1c subgroup 30–32 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Changes in weight across all dulaglutide dose groups, as well as dose‐related treatment differences in weight loss, were larger among patients with lower (<8.5% [69 mmol/mol]) versus higher (≥8.5%) baseline HbA1c. This is consistent with prior studies suggesting an inverse relationship between the magnitude of GLP‐1 RA‐mediated weight loss and baseline HbA1c 21,29,30 . The physiological basis for this phenomenon is not clear, but could be related to greater reductions in energy loss through glucosuria following greater improvements in glycaemic control observed in the higher baseline HbA1c subgroup (and thus poorer baseline glycaemic control) compared with the lower baseline HbA1c subgroup 30–32 .…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with prior studies suggesting an inverse relationship between the magnitude of GLP‐1 RA‐mediated weight loss and baseline HbA1c. 21 , 29 , 30 The physiological basis for this phenomenon is not clear, but could be related to greater reductions in energy loss through glucosuria following greater improvements in glycaemic control observed in the higher baseline HbA1c subgroup (and thus poorer baseline glycaemic control) compared with the lower baseline HbA1c subgroup. 30 , 31 , 32 In other words, weight loss may be partially mitigated by greater calorie (energy) retention dictated by the diminished glucosuria occurring in subjects with more pronounced baseline hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…This result was not consistent with subgroup analyses of the global PIONEER trials, in which there were no apparent patterns between the change in bodyweight and baseline HbA 1c 26 . For once‐weekly s.c. semaglutide, baseline HbA 1c did significantly affect the change from baseline in bodyweight in a global population, with weight loss decreasing as baseline HbA 1c increased 27 . In addition, the subgroup analysis of Japanese patients receiving dulaglutide 0.75 mg also found that lower baseline HbA 1c was significantly associated with greater bodyweight changes from baseline 28 .…”
Section: Discussionmentioning
confidence: 90%
“…A subgroup analysis of the global PIONEER 1–5, 7, and 8 trials, which used the same HbA 1c cut‐offs as the present analysis, also found that HbA 1c reductions from baseline were greater in patients with higher baseline HbA 1c compared with lower baseline HbA 1c 26 . This pattern was also observed in a subgroup analysis of once‐weekly s.c. semaglutide in a global population, although that analysis had a greater number of HbA 1c subgroups 27 . Furthermore, similar findings were also observed in subgroup analyses of Japanese patients who received other GLP‐1RAs, specifically dulaglutide 0.75 mg 28 and lixisenatide 20 μg 29 .…”
Section: Discussionmentioning
confidence: 94%
“…Notably, patients with higher baseline HbA1c experienced greater estimated treatment differences in HbA1c with oral semaglutide compared to placebo. A greater glycaemic response at higher baseline HbA1c levels is a known phenomenon as baseline HbA1c is often a predictor of glycaemic response for many glucose‐lowering treatments, 19 including other glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) 20‐23 and once‐weekly subcutaneous semaglutide 24 . Since this phenomenon also applies to other glucose‐lowering treatments, it is not surprising that HbA1c level had less impact on the magnitude of estimated treatment differences in trials with an active comparator.…”
Section: Discussionmentioning
confidence: 99%